The Thai Anesthesia Incidents Study (THAI Study) of perioperative allergic reactions - Thienthong S. (2014)
Objectives: To determine the incidence, risk factors, signs, symptoms and management of perioperative allergic reactions in the Thai Anesthesia Incidents Study (THAI Study). Material and Method: Between February 1, 2003, and January 31, 2004, a descriptive, prospective, multicenter study was conducted in 20 hospitals across Thailand. All patients receiving anesthetic and medical agents were monitored for allergic reactions for the first 24 postoperative-hours. Signs and symptoms of suspected allergic reactions included skin reactions, wheezing and unexpected hypotension. The details of allergic reactions were reviewed and recorded. Results: Allergic reactions occurred in 30 of the 163,403 patients included in this study. The reaction-incidence was approximately 1 in 5,500 cases of anesthesia. Forty-eight percent of the affected patients had a history of allergic reactions. The manifestations were skin reactions, hypotension and wheezing in 38, 22 and 19 percent of the overall symptoms, respectively. Reactions were mild, moderate and severe in 40, 23 and 37 percent of the patients, respectively. The three drugs most suspected of causing the reaction(s) were antibiotics (19%), muscle relaxants (17%) and propofol (15%). All of the affected patients recovered after treatment including the one who suffered cardiac arrest because of the allergic reaction. Conclusion: The incidence of perioperative allergic reactions was 1 in 5,500 cases of anesthesia. History of allergies was obtained from half of the patients and the most common sign was a skin reaction. The drugs most suspected of causing an allergic reaction were antibiotics. All of the patients responded well to rescue treatment.